2013
DOI: 10.1007/s00068-013-0285-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acidosis is associated with multiple organ failure and need for ventilator support in patients with severe hemorrhage from trauma

Abstract: Elevated blood lactate levels from trauma were closely correlated with worse outcomes. Thus, lactate shows promise as a biomarker for resuscitation as well as a predictor of mortality. Furthermore, this study supports its use in critical care trials as an outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Lefering ET cols 6 demonstrated correlation of serum lactate levels with mortality, with the highest levels present in patients with late mortality, after 48 h of admission. In this study, no correlation was found between lactate and death, either early or late.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Lefering ET cols 6 demonstrated correlation of serum lactate levels with mortality, with the highest levels present in patients with late mortality, after 48 h of admission. In this study, no correlation was found between lactate and death, either early or late.…”
Section: Discussionmentioning
confidence: 95%
“…Lactate is a product of anaerobic metabolism and can be used as a marker of hypoxia in different states of shock. Elevated serum levels on admission of multiple trauma patients is related to higher mortality 3 5 7 15 , higher mortality in patients affected by septic shock 6 and predict blood products need and also may aid in the early detection of severity 3 . Several researchers have established the use of lactate as a diagnostic and prognostic marker of severity and mortality 1 7 9 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial high lactate level on admission of patients with multiple traumas is correlated with higher mortality rates 18 -21 . Because of higher death rate patients affected by septic shock 22 and predicting the need for blood products, it can also help to diagnose severity early 19 . The use of lactate as an indicator of severity and mortality was established by several investigators 14, 18 -20, 22 -24 .…”
Section: Discussionmentioning
confidence: 99%